PKM Peningkatan Kemampuan Pengolahan Produk Hasil Perikanan Bagi Istri Nelayan dan Ibu Rumah Tangga Desa Batu Putih - Suwarjoyowirayatno; Gebriella Inthe, Mita; Syukri Sadimantara, Muh; Sakir; Daniningsih, Tri (Amaliah: Jurnal Pengabdian Masyarakat, 2025)
Batu Putih is village is located in coastal area of East Kolono Subdistrict, South Konawe Regency, Southeast Sulawesi Province. As a coastal area, this village has good potential in fisheries products. This potential is not utilized well, when the fish catches are abundant, but not all fishes was utilized properly, even wasted due to damage, whereas if fishes was difficult to obtained, so that people lack of protein sources for consumption. This happened because lack of the knowledge of the community in processing fisheries products to maintain their quality and storability. The Community Partnership Program (CPP) aims to provide knowledge and skills to the fisherman wives and housewives of Batu Putih Village on how to handling, processing and marketing of fisheries products. The program is conducted using action research method consist of giving presentation, training and practice. The results of the data obtained that 86% of participants have never attended training in fisheries processing product and 14% have already been. Data from participants who have made fisheries products is known that 66.7% of participants have never made fish meatballs, 19% have been once and 14.3% have been more than once, while for Pempek products, anchovies chips, amplang fish, candied seaweed and seaweed mango juice was 100% of participants have never made it. Therefore, this program was very appropriate given to the community to improve their knowledge and skills. The result of this program is that the community gets an increased in knowledge about post-catch handling, processing fisheries products, packaging, product legality, marketing, and improving skills by practicing to made of fisheries products directly.